Culture clubs consultation 2018 : "preserving Jamaica's cultural heritage through technology and integration" Eastern Region - Jamaica Cultural Development Commission (Kingston, Jamaica : JCDC, 2018)
This programme was designed for the "Culture Clubs Consultation 2018, Eastern Region". The event was held at the Alfred Sangster's Auditorium, UTECH, on Thursday, November 29, 2018 at 9:00 am under the theme "Preserving Jamaica's Cultural Heritage Through Technology and Integration".
Keywords: Programmes. -- Jamaica